Abiola Irele and the anti-Négritude1 generation: "In Praise of Alienation". Issue 1 (2nd January 2020) - Kemedjio, Cilas
ABSTARCT: In this article, I read Abiola F. Irele's "In Praise of Alienation" as a departure from the "going native" cultural nationalism that was sparked by the black renaissance cultural movements, including the African and Caribbean francophone movement of Négritude. "In Praise of Alienation" appears as a manifestation of the anxieties expressed by an entire generation in the face of the collapse of the dreams sparked by the anticolonial struggles. From locating Abiola Irele within intellectual and cultural movements that took place in the Black Paris, this article, in a more meditative and personal note, turns to what may be considered part memorial, part memoir, part tribute to a literary critic whose mantra was "the ideology of relevance" of the African intellectual.